Prognostic factors and predictive scores for 6-months mortality of hematopoietic stem cell transplantation recipients admitted to the pediatric intensive care unit - Schober, Sarah; Huber, Silke; Braun, Norbert; Döring, Michaela; Lang, Peter; Hofbeck, Michael; Neunhoeffer, Felix; Renk, Hanna (Frontiers in Oncology, 2023)
Objective: Despite advances in hematopoietic stem cell transplantation (HSCT), a considerable number of pediatric HSCT patients develops post-transplant complications requiring admission to the pediatric intensive care unit (PICU). The objective of this study was to evaluate clinical findings, PICU supportive therapy and outcome as well as predictive factors for 6-months survival after discharge of HSCT patients from PICU. Study design: This retrospective single-center analysis investigated patient characteristics, microbiological findings, reasons for admission and death of 54 cases accounting for 94 admissions to the PICU of the University Children’s Hospital Tuebingen from 2002 to 2017. We compared clinical characteristics between children with and without 6-months survival after discharge from PICU following HSCT. Finally, we assessed the potential prognostic value of the oncological Pediatric Risk of Mortality Score (O-PRISM), the Pediatric Sequential Organ Failure Assessment Score (pSOFA) and the pRIFLE Criteria for Acute Kidney Injury for 6-months survival using Generalized Estimating Equations (GEE) and Receiver Operating Characteristic curves. Results: Respiratory insufficiency, gastroenterological problems and sepsis were the most common reasons for PICU admission. Out of 54 patients, 38 (70 %) died during or after their last PICU admission, 30 % survived for at least six months. When considering only first PICU admissions, we could not determine prognostic factors for 6-months mortality. In contrast, under consideration of all PICU admissions in the GEE model, ventilation (p=0.03) and dialysis (p=0.007) were prognostic factors for 6-months mortality. Furthermore, pSOFA (p=0.04) and O-PRISM (p=0.02) were independent risk factors for 6-months mortality considering all PICU admissions. Conclusions: Admission of HSCT patients to PICU is still associated with poor outcome and 69 % of patients died within 6 months. Need for respiratory support and dialysis are associated with poor outcome. Prediction of 6-months survival is difficult, especially during a first PICU admission. However, on subsequent PICU admissions pSOFA and O-PRISM scores might be useful to predict mortality. These scores should be prospectively evaluated in further studies to verify whether these scores can identify pediatric HSCT recipients profiting most from transferal to the PICU.